Effect of Macroprudential Policy on Banks’ Profitability in ASEAN Before and During Covid-19 - Tarigan, Wina Febrianti; Danarsari, Dwi Nastiti (Jurnal Keuangan dan Perbankan, 2023)
Regulators introduced macroprudential policies to ensure financial stability, but during the Covid-19 pandemic, many countries relaxed these policies to boost credit growth and the economy. This research examines the impact of these policies on bank profitability in six ASEAN countries from 2018 to 2021 using panel data regression. Before the pandemic, tightening policies like capital buffers, taxes, liquidity requirements, and foreign exchange limits reduced bank profitability. During the pandemic, loosening loan loss provisions and loan-to-value ratios increased profitability, while relaxing reserve requirements decreased it. DOI: 10.26905/jkdp.v27i3.10283